Coastal upward discharge of deep basalt groundwater through developed faults: A case study of the Subei Basin, China. (15th March 2022) - Ma, Fenyan; Chen, Jiansheng; Zhan, Lucheng; Wang, Tao; Yan, Jiaheng; Zhang, Xi
Abstract: The relationship between groundwater and seawater is sensitive to groundwater exploitation, thus, not a simple result of groundwater and seawater lateral flow. The upward recharge of deep groundwater leads to a more complex relationship between groundwater and seawater in coastal regions with developed faults. The Quaternary confined groundwater level is significantly decreased in the case of groundwater overexploitation in the coastal region of the Subei Basin, where active faults are developed. The water level and hydrochemistry data for confined groundwater during periods of groundwater overexploitation was analyzed in the Subei Basin. Results show that confined groundwater is negligibly affected by seawater intrusion, while groundwater desalination is apparent during this period. High confined groundwater levels have been observed for many years in the area with intense groundwater exploitation. Additionally, the chemical and stable isotopic characteristics of confined groundwater, phreatic water, and surface water in the study area were investigated to reveal the pathways and origin of deep groundwater. The hydrogeochemical results demonstrate that the confined groundwater originates from basalt groundwater and is related to deep circulation. The active faults in the study area serve as pathways for upward recharge of basalt groundwater. Our findings provide new insights into the relationship between groundwater and seawater, and indicate that the upward recharge of deep groundwater should be considered in coastal regions with developed faults. Graphical abstract: Image 1 Highlights: Quaternary groundwater desalinated, minimally affected by seawater intrusion with overexploitation in the coastal region, Subei. High groundwater level with intense exploitation related to deep groundwater recharge through faults. Metasilicic acid mineral water in the Quaternary aquifer related to deep circulation and concealed basalt formations.